UNSILENCING THE SILENT SOUTH AFRICAN HIV-POSITIVE RESEARCHER: AN HIV-POSITIVE RESEARCHER’S REFLECTION ON NEGOTIATNG INSIDER- OUTSIDER POSITIONALITIES WHILEST CONDUCTING A HIV STUDY IN eTHEKWINI, KWAZULU-NATAL, SOUTH AFRICA - Mulqueeny, Delarise Maud; Taylor, Myra (Social Work/Maatskaplike Werk, 2019)
The research study that informed this article’s discussion, critically interrogates an HIV-infected research team’s positionality whilst conducting a mixed-methods’ study on HIV-positive patients’ experiences of the public ART programme at four ARV clinics in KwaZulu-Natal, South Africa. It primarily utilises the principal investigator’s (PI) narrative to explore insider/outsider positionality, reflexivity, bracketing and participatory action research through exposure of feelings, emotions, challenges, engagements, relationships and observations. The fluid positionality of the HIV-positive research team presented both challenges and opportunities. However, the opportunities for more HIV-infected researchers to engage in HIV-related research to assist with destigmatising HIV, close research gaps and the creation of a trustworthy research environment to achieve an ethical and reliable health science study, far outweigh the challenges. Further, such research can improve patients’ support and healthcare, healthcare workers’ perceptions of patients, and provide a guide for policymakers to better understand the recipients of HIV policies. Lastly, the term ‘HIV reflexivity’ is coined as a result.